1996
DOI: 10.1039/cc9960002235
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of B–B π-bonding in singly reduced and neutral diborane (4) derivatives: isolation and structure of [{Li(Et2O)2}{MeO(mes)BB(mes)OMe}]

Abstract: A single-crystal X-ray diffraction study of [ {Li(Et20)2}-{ MeO(mes)BB(mes)OMe}] 1 (mes = C6H2Me3-2,4,6) allows the first structural comparison between singly reduced and neutral diborane(4) species; compound 1, features a shortened B-B bond distanc? of 1.636(7) A which may be compared to the 1.724(9) A observed in the neutral precurso: MeO(mes)BB(mes)OMe 2 and a distance of 1.62-1.64 A observed in related doubly reduced [R2BBR2]2-species; the B-B bond in 1, which has a formal a-bond order of 0.5, is thus simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 21 publications
4
53
0
6
Order By: Relevance
“…Their use has resulted in the stabilization of many new compound classes including the first crystalline heavier group 14 radicals (GeAr # ) 3 [24], the multiply bonded species Na 2 Ar * MMAr * (M = Ge, Sn) [25] or [K(THF) 6 ][Ar * SnSnAr * ] [26], Cp(CO) 2 M"GeAr # (M = Mo, W) [27], Cp(CO) 2 M"GeAr * (M = Cr, Mo, W) [28], trans-[Cl(PMe 3 ) 4 W"SnAr * ] [29], trans-[Br(PMe 3 ) 4 Mo" PbAr * ] [30], alkene and alkyne analogs of groups 13 and 14 elements Na 2 [Ar * GaGaAr * ] [31] and Ar 0 MMAr 0 (M = Al [21], Ga [32], In [33], Ge [17], Sn [18], Pb [19]) or the hydride (Ar * SnH) 2 [13]. Attempts to extend the range of such compounds to include boron or silicon species such as ArBBAr or ArSiSiAr have encountered problems with activation of the substituents on the flanking aryls that yield products incorporating boron [34][35][36] or silicon [37][38][39][40][41][42][43] in the rings rather than the desired multiply bonded species. However, in parallel work by Rothwell and coworkers on related 2,6-diarylphenoxide ligands [44], it has been shown that the introduction of alkyl groups on the central aryl ortho to the flanking aryl rings confers lower susceptibility, if not immunity, to undesirable reactions of this type.…”
Section: Introductionmentioning
confidence: 98%
“…Their use has resulted in the stabilization of many new compound classes including the first crystalline heavier group 14 radicals (GeAr # ) 3 [24], the multiply bonded species Na 2 Ar * MMAr * (M = Ge, Sn) [25] or [K(THF) 6 ][Ar * SnSnAr * ] [26], Cp(CO) 2 M"GeAr # (M = Mo, W) [27], Cp(CO) 2 M"GeAr * (M = Cr, Mo, W) [28], trans-[Cl(PMe 3 ) 4 W"SnAr * ] [29], trans-[Br(PMe 3 ) 4 Mo" PbAr * ] [30], alkene and alkyne analogs of groups 13 and 14 elements Na 2 [Ar * GaGaAr * ] [31] and Ar 0 MMAr 0 (M = Al [21], Ga [32], In [33], Ge [17], Sn [18], Pb [19]) or the hydride (Ar * SnH) 2 [13]. Attempts to extend the range of such compounds to include boron or silicon species such as ArBBAr or ArSiSiAr have encountered problems with activation of the substituents on the flanking aryls that yield products incorporating boron [34][35][36] or silicon [37][38][39][40][41][42][43] in the rings rather than the desired multiply bonded species. However, in parallel work by Rothwell and coworkers on related 2,6-diarylphenoxide ligands [44], it has been shown that the introduction of alkyl groups on the central aryl ortho to the flanking aryl rings confers lower susceptibility, if not immunity, to undesirable reactions of this type.…”
Section: Introductionmentioning
confidence: 98%
“…The resulting diborane(4) radical , in which the Li + cation is bound to the anion by coordination to the methoxy oxygens. 7 The broadness of the electron paramagnetic resonance (EPR) signal of this paramagnetic species precluded the determination of hfcc values. However, the solvent-separated ion pair, [K(18-crown-6)(THF) 2 ][Mes 2 BB(Ph)Mes], which was obtained by one-electron reduction with potassium in tetrahydrofuran (THF) followed by the addition of 18-crown-6, exhibits a seven-line EPR pattern (g = 2.0063) with a( 11 B) = 13 G due to the coupling to two boron centers ( 11 B, I = 3/2, 80.2 %) consistent with the formation of a π radical.…”
Section: Radical Anions/early Studiesmentioning
confidence: 99%
“…[31] Diese Zwischenstufen mit einer B-B-Bindungsordnung von 1.5 können als gleichwertig zu Kationenradikalen von Olefinen betrachtet werden, und die EPR-Hyperfeinkopplung der direkt verbundenen Boratome wird stark durch Strukturfaktoren beeinflusst, wie kristallographische Untersuchungen ergaben. [32] 2.2. R 2 B-Substituierte N-Heterocyclen Systeme wie 1 oder 2 lassen sich durch Substitution der Bor-bindenden Ringkohlenstoffatome durch Stickstoff (5, 6) modifizieren.…”
Section: Durch Bor Alsunclassified